Implementasi Bahasa Python Dalam Menganalisis Pengaruh Rokok Terhadap Risiko Pasien Terkena Penyakit Stroke - Kairos Abinaya Susanto; Darrien Rafael Wijaya; Matthew Owen; Tertius Raya Prasetya; George Maximillian Theodore; Jevant Russell; Rahmi Yulia Ningsih (Pusat Riset dan Inovasi Nasional, 2023)
This study discusses the implementation of Python programming language in analyzing the influence of smoking habits on the risk of stroke in patients. The study utilizes the